Positive Solutions for System of Nonlinear Fractional Differential Equations in Two Dimensions with Delay - Azizollah Babakhani (Abstract and Applied Analysis)
We investigate the existence and uniqueness of positive solution for system of nonlinear fractional differential equations in two dimensions with delay. Our analysis relies on a nonlinear alternative of Leray-Schauder type and Krasnoselskii's fixed point theorem in a cone.